PENGEMBANGAN MODEL BANTUAN BERBASIS MENTORING UNTUK PUBLIKASI ARTIKEL ILMIAH MAHASISWA DI JURNAL NASIONAL TERNAMA - Shadry Andriani; Abd. Rahim; Diah Retno Dwi Hastuti; Himaya Praptani Adys; Ahmad Faqhruddin Abdur-Rabb (Jurnal Akademik Pengabdian Masyarakat Ichsan Sidrap, 2026)
This research aims to develop a mentoring-based mentoring model in order to improve the quality of student scientific article publications in nationally reputable journals. The mentoring process designed through a series of stages including: preparation, development, finalization, and evaluation. The preparation stage includes collecting students who already have draft articles, scheduling, and adjusting articles to the templates and guidelines of the intended journal. At the development stage, students are given guidance in adjusting the article to the needs of the journal. At the finalization stage, the article is re-examined to ensure compliance with journal guidelines and the article is submitted to a nationally reputable journal. The evaluation stage is carried out by asking students to conduct post-publication reflections, calculating the percentage of students who have successfully published articles in reputable journals and the results of 20 students who participated in this training activity there were 10 students who successfully submitted to national reputable journals and 2 others at the review process stage. The results of this study indicate that a mentoring-based assistance model can improve students' academic writing skills and processes, as well as chances of publishing articles in reputable national journals.